A STUDY ON THE ABILITY OF SECOND SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF FKIP MUHAMMADIYAH UNIVERSITY OF MALANG TO IMPROVE COMPREHENDING ENGLISH TEXTS - muhammad arif wahyudi (JURNAL ILMIAH BAHASA DAN SASTRA, 2014)
ABSTRACT: Reading is one of language skill, which must be developed with practice. The students learn how to read well in order to comprehend texts, either in a short text or long one. The researcher got research at English Department of FKIP of Muhammadiyah University of Malang especially Second Semesters that had a problem to comprehend English Text. The data collected from the reading test were analyzed to find the answer of problem. The steps in process were as follows: firstly, the writer corrected the student’s answer sheets; secondly, give score for each answer sheet, thirdly, identified the student’s score. This study uses descriptive method by collecting data in order to answer the question concerning status of subject of study. The subjectis second semesters that consist of 200 of students. The instrument uses to collect the data is reading test that are to know their ability in English text.The result of the analyzing of available can be interpreted that the students of English Department have mastered the English texts, and many students get problem namely 32 the students getting high score, 8 students getting lower score and the mean of value reliability items are 12,425. It means that the student’s ability in comprehending texts is good. It is hoped that teacher will make to use of this findings by giving more attention to comprehend English text in teaching and learning of English so that the student’s ability in comprehending texts can be improve.